2018
DOI: 10.5114/bta.2018.73559
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioactive metabolites from different marine endophytic Streptomyces species and testing them against methicillin-resistant Staphylococcus aureus (MRSA) and cancer cell lines

Abstract: The aim of the work was to identify Actinomycetes strains that are able to produce high levels of anti-MRSA metabolites with a potential use in curing resistant Staphylococcus aureus infections. Twenty-six endophytic Actinomycetes strains were isolated from various marine invertebrates living in two different marine ecosystems (the Mediterranean Sea and the Red Sea). Among them, Streptomyces sp. RS-9 (obtained from the soft coral Sarcophyton sp. from the Red Sea) and Streptomyces sp. MS-26 (obtained from the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…They were catalase and methyl red tests positive ( Figure 6). In accordance with our data, previously studies reported that S. aureus isolates grown on blood agar with β-hemolysis activity and on mannitol salt agar medium, which considered a selective and differential medium for S. aureus turned its color from red to yellow as a result of mannitol fermentation and acid production and they are positive for catalase, coagulase and MR-VP tests but negative for indole test [5,[23][24][25]. Also, Shah and Panchal, stated that S. aureus isolates are snowy, creamy to gold color and as Gram positive cocci with β-haemolysis on blood agar and proteolysis on casein agar plates [3].…”
Section: Isolation Morphological and Biochemical Characterization Ofsupporting
confidence: 91%
See 2 more Smart Citations
“…They were catalase and methyl red tests positive ( Figure 6). In accordance with our data, previously studies reported that S. aureus isolates grown on blood agar with β-hemolysis activity and on mannitol salt agar medium, which considered a selective and differential medium for S. aureus turned its color from red to yellow as a result of mannitol fermentation and acid production and they are positive for catalase, coagulase and MR-VP tests but negative for indole test [5,[23][24][25]. Also, Shah and Panchal, stated that S. aureus isolates are snowy, creamy to gold color and as Gram positive cocci with β-haemolysis on blood agar and proteolysis on casein agar plates [3].…”
Section: Isolation Morphological and Biochemical Characterization Ofsupporting
confidence: 91%
“…the highest microbial growth 7.90 and 7.82 log CFU/mL recorded with fructose and glucose as well as 8.00 and 8.90 log CFU/mL obtained with beef extract and yeast extract but growth values markedly increased with adding amino acid alanine, glycine, histidine and lysine to reach 10.15, 11.93, 10.00 and 11.19 log CFU/mL, respectively. Consistent with literature sources, the optimum temperature for the growth of S. aureus was ranged from 37 to 40 °C as well as beef extract, dextrose and NaCl were reported as the most suitable parameters [18,23,24].…”
Section: Quantitative Evaluation Of Staphylokinase Activity In Clinicsupporting
confidence: 70%
See 1 more Smart Citation
“…Most of these compounds were isolated from terrestrial sources (Barka et al, 2016;Van Der Meij et al, 2017). However, there were reports recently, where their marine counterparts were also recognized as a source of bioactive compounds (Shaik et al, 2017;Yang and Song, 2017;El-Gendy et al, 2018;Kemung et al, 2018;Subramani and Sipkema, 2019). The condition in the marine environment is remarkably different from that of the terrestrial environment.…”
Section: Resultsmentioning
confidence: 99%
“…They gain increasing concern due to their facility for withstanding the in luence of various antibacterial agents, accordingly limit the drug of choices and leads to higher mortality and morbidity [4]. Therefore, inding of alternate powerful, inexpensive and harmless natural agents against multidrug resistant bacteria can be potent way for solving this serious global problem [5][6][7]. Marine bacteria are promising reservoirs of diverse effective bioactive natural products and many of them are being used in chemotherapy to treatment human diseases especially with the continuing need for new potent compounds against drug-resistant pathogens and https://doi.org/10.29328/journal.abb.1001018 managing of distressing cancers with high selective activity and less toxicity [8,9].…”
Section: Introductionmentioning
confidence: 99%